Las canciones infantiles y las habilidades comunicativas en la enseñanza semipresencial en niños de cinco años de la Institución Educativa Inicial N° 752 Ramón Castilla, Caballococha 2022 - Loayza Herrera, Noemi (2022)
This has been advanced with the intention of arguing the level of relationship between children's songs and communication skills in teaching blended study in five-year-old children of the Initial Educational Institution No. 752 District of Ramón Castilla- Caballo Cocha 2022, El The study was relevant and had a non-experimental design. The populace comprised of 5-year-old young men and young ladies from essential training organizations. Observation as a technique and the observation guide as a tool for obtaining pre-validated data through expert judgments. It was concluded that there is a significant connection between nursery rhymes and blended written communication for 5-year-old children from the primary school of District 752 Ramón Castilla-Cabalo Cocha, 2022. In this reason, it is validated with the Pearson connection coefficient ( r) with a value of 0.005, which is high and direct.